Spinning an entrepreneurial career: Motivation, attribution, and the development of organizational capabilities - Lee, Hyeonsuh; Shah, Sonali K.; Agarwal, Rajshree (Strategic Management Journal, 2024)
Abstract Research Summary We inductively examine how the careers of employee entrepreneurs unfold, uncovering the role of motives and attribution for failure. Founders expressing organizational misalignment motives for leaving established organizations engaged in “venture crafting” whereby they actively sought to build well‐functioning organizations. They built successful initial ventures and careers. Founders lacking organizational misalignment motives generally founded initial ventures that failed: however, those making internal attributions altered their behaviors and built successful careers; in contrast, founders making external attributions continued founding unsuccessful ventures. These findings suggest that building organizational capabilities—and not merely inheriting capabilities from existing organizations—is a cornerstone of building successful entrepreneurial careers. Our findings are based on detailed career history and archival data on employee entrepreneurs in the disk‐drive industry. Managerial Summary Our study follows careers of individuals leaving employment to create ventures, providing insights for entrepreneurs and managers. Though entrepreneurs often choose to focus solely on building a stellar product, our study underscores the importance of crafting well‐functioning organizations for career and venture success. Moreover, in case where initial ventures fail, founders who make internal attribution generate a “second chance” at success, whether as serial entrepreneurs or by returning to paid employment. Those who attribute failure to external factors, however, repeat their mistakes. For managers, our study reveals that the genesis of successful entrepreneurial careers is rooted in organizational deficiencies that prevent talented employees from thriving as intrapreneurs. The venture crafters typically left their jobs only after attempts to amend these issues were unsuccessful.